Emotions as Affective Position-Takings and as Nonconceptual Meta-Representations: A Comparison. (October 2022) - Reisenzein, Rainer
The theory of emotions as affective position-takings (PT) is investigated from the perspective of a computational model of the belief-desire theory of emotions (CBDTE) proposed by the author. Both theories assume that a core subset of typical emotion episodes are the products of an evaluation process in which cognized states of affairs are evaluated for their congruence with the person's desires; and that emotions are, on the conscious level, feelings of pleasure and displeasure. However, according to PT the evaluation is a concern-based construal and emotional feelings are intrinsically object-directed, whereas according to CBDTE, the evaluation is performed by a hardwired mechanism that produces nonintentional feelings. Furthermore, CBDTE suggests that hedonic feelings are simultaneously reactions to the detection of value, and representations of the detected value.